Kajian Kritis Terhadap Pemikiran Tentang Jiwa (Al-Nafs) dalam Filsafat Islam - Asriyah, Asriyah (Jurnal Adabiyah, 2010)
The very sugnificant element in this life is soul. It is immaterial aspect influencing the way of human life. Althought it existed in one’s body, but it cannot be seen and even constructurally seperated from body. The soul is usually become the object of sufi orders. By exploring this potency, they try to reach the highest top of spirituality, till they feel the “God consciousness.